2021
DOI: 10.7759/cureus.14001
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Viability of Motor Imagery as a Physical Rehabilitation Treatment for Patients With Stroke-Induced Motor Cortical Damage

Abstract: Although around 83% of individuals survive a stroke, they usually experience a significant loss in their motor execution (ME) capabilities due to their acquired cortical infarction. The loss of significant ME capabilities due to stroke damage was previously thought to be irreversible. Active movement therapies show considerable promise but depend on motor performance, excluding many otherwise eligible patients. Motor imagery (MI), a process that involves the use of mirror neurons to imagine motor activity, has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…These techniques are based on the theory of mirror neurons and demonstrate that people can produce plastic changes in the functionality of hand movements. Several studies have identified patterns in brain activation that occur during MI and found that MI largely activates regions including the frontoparietal network, subcortical and cerebellar regions, anterior intraparietal cortex, primary motor cortex (M1), bilateral supplementary area (SMA), and premotor area (PMA) [12]. Another study [13] showed that the use of MI improves a patient's upper limb motor functions and activation areas mentioned in the previous study.…”
Section: Introductionmentioning
confidence: 92%
“…These techniques are based on the theory of mirror neurons and demonstrate that people can produce plastic changes in the functionality of hand movements. Several studies have identified patterns in brain activation that occur during MI and found that MI largely activates regions including the frontoparietal network, subcortical and cerebellar regions, anterior intraparietal cortex, primary motor cortex (M1), bilateral supplementary area (SMA), and premotor area (PMA) [12]. Another study [13] showed that the use of MI improves a patient's upper limb motor functions and activation areas mentioned in the previous study.…”
Section: Introductionmentioning
confidence: 92%
“…Therefore, regions within the primary motor cortex, cerebellum, and basal ganglia circuits can be activated during MI ( Kraft et al, 2015 ; Tong et al, 2017 ). In addition, MI can also induce the functional redistribution and regulation of neural circuits, remodeling the brain neural networks, and improving motor function relearning ability ( de Vries and Mulder, 2007 ; Gowda et al, 2021 ). Furthermore, repeated training can form a normal motor reflex arc, thus, promoting limb function recovery in the stroke patients ( Grabherr et al, 2015 ; López et al, 2019 ; Ladda et al, 2021 ).…”
Section: Motor Imagery Trainingmentioning
confidence: 99%
“…This causes abnormal involuntary coupling between shoulder visitation and wrist/finger flexion (flexion synergy), as well as weakness in the muscles that are the extensors of the distal joints. This results in a significant limitation of hand opening movement [41,42].…”
Section: Introductionmentioning
confidence: 99%